Dynamics of a piecewise-linear oscillator with limited power supply - De Souza, Silvio L.T.; Caldas, Iberê L.; Balthazar, José Manoel [UNESP]; Brasil, Reyolando M.L.R.F. (ASME International, 2009)
We discuss dynamics of a vibro-impact system consisting of a cart with an piecewise-linear restoring force, which vibrates under driving by a source with limited power supply. From the point of view of dynamical systems, vibro-impact systems exhibit a rich variety of phenomena, particularly chaotic motion. In our analyzes, we use bifurcation diagrams, basins of attractions, identifying several non-linear phenomena, such as chaotic regimes, crises, intermittent mechanisms, and coexistence of attractors with complex basins of attraction. © 2009 by ASME.
Keywords: Basins of attraction; Bifurcation diagram; Chaotic motions; Intermittent mechanism; Limited power supply; Non-linear phenomena; Piecewise-linear; Restoring forces; Vibro impact system; Design; Dynamical systems; Piecewise linear techniques; Vibrators; Dynamics